Instability of the Perceived World While Watching 3D Stereoscopic Imagery: A likely Source of Motion Sickness Symptoms. (October 2014) - Hwang, Alex D.; Peli, Eli
Watching 3D content using a stereoscopic display may cause various discomforting symptoms, including eye strain, blurred vision, double vision, and motion sickness. Numerous studies have reported motion-sickness-like symptoms during stereoscopic viewing, but no causal linkage between specific aspects of the presentation and the induced discomfort has been explicitly proposed. Here, we describe several causes, in which stereoscopic capture, display, and viewing differ from natural viewing resulting in static and, importantly, dynamic distortions that conflict with the expected stability and rigidity of the real world. This analysis provides a basis for suggested changes to display systems that may alleviate the symptoms, and suggestions for future studies to determine the relative contribution of the various effects to the unpleasant symptoms.